Dampak Pembelajaran Berbasis Proyek terhadap Pemahaman Konsep Statistika Mahasiswa PGSD UNM - A. Muhajir Nasir; Latri Aras (Program Studi Pendidikan Matematika, FKIP Universitas Muslim Maros, 2025)
This study aims to analyze the impact of implementing the Project-Based Learning (PBL) model on the conceptual understanding of statistics among students of the Primary School Teacher Education (PGSD) program at Universitas Negeri Makassar. The research employed a quantitative method with a post-test only design, involving 91 randomly selected students as the sample. Data were collected through a post-test in the form of a project assignment and a student perception questionnaire on PBL. The results showed that most students had a positive perception of the PBL method, with an average perception score of 76.15 and a learning outcome score of 84.99. Pearson correlation analysis indicated a weak positive relationship between students' perceptions of PBL and their learning outcomes (r = 0.215), suggesting that other factors such as motivation and learning styles may have a greater influence. Nevertheless, PBL was shown to improve students' understanding of statistical concepts in general. This study recommends enhancing the quality of PBL implementation and developing more contextual and interactive learning strategies within the PGSD environment.